NUTQI TO‘LIQ RIVOJLANMAGAN BOLALAR MULOQATINI ERTAKLAR ASOSIDA RIVOJLANTIRISH VA UNING NATIJALARI - Tajimuratova, K.; Tajimuratov, A. (FAN va JAMIYAT, 2024)
This article highlights the importance of using folktales in the correction of preschool children whose speech is not fully developed.